2009
DOI: 10.1016/j.apenergy.2008.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Optimization as investment decision support in a Swedish medium-sized iron foundry – A move beyond traditional energy auditing

Abstract: Due to increased globalisation, industries are facing greater competition that is pressing companies into decreasing their expenses in order to increase their profits. As regards Swedish industry, it has been faced with substantial increases in energy prices in recent years. Barriers to energy efficiency such as imperfect information inhibit investments in energy efficiency measures, energy audits being one means of reducing barriers and overcoming imperfect information. However, an evaluation of such energy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 16 publications
0
25
0
2
Order By: Relevance
“…Matos and Silvestre, 2013;Rauter et al, 2015). In such research, optimization as an investment decision support, such as the so-called 'MIND-method', can be used (Thollander et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Matos and Silvestre, 2013;Rauter et al, 2015). In such research, optimization as an investment decision support, such as the so-called 'MIND-method', can be used (Thollander et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…pulp and paper, forest, automobile manufacturing and chemical) to study both economic and environmental aspects (e.g. CO2 emission impact) [25][26][27][28]. A more through description of the method can be found in [21].…”
Section: Energy Systems Modeling Toolmentioning
confidence: 99%
“…Basically, the analysis in reMIND includes four steps [2,32,37]. In the first step, the real system has to be delimited.…”
Section: Energy Systems Optimisation (Eso) Toolmentioning
confidence: 99%
“…However, it has been shown that many of these difficulties may be solved by DES and ESO tools [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The ESO tool has been used in several industries, such as the Swedish foundry industry [2], steel industry [3,4] and pulp and paper mills [5,6], as well as in district heating systems [7] and waste treatment [8].…”
Section: Introductionmentioning
confidence: 99%